Immunologic Reactivity in Adolescents with Duodenal Ulcer - L.K. Parkhomenko; L.A. Strashok; E.M. Zavelia; M.Yu. Isakova; A.V. Yeshchenko; T.V. Yevdokimova (Zaslavsky O.Yu., 2015)
The article presents the results of studying immunological and cytokine status in adolescents with duodenal ulcer. Duodenal ulcer is associated with increased levels of interleukin (IL)-1β, IL-4, IL-6 and the decrease in the content of tumour necrosis factor α (TNF-α), T-cells. In the inflammatory infiltration of the gastric and duodenal mucosa in duodenal ulcer, there is a high density of cells producing IL-1β, IL-4, IL-6, a small amount of cells producing TNF-α that correlates with their content in the blood serum.